Between Intention and Integration Stakeholder Coordination and Energy Resilience: A Comparative Case Study of Copenhagen and Stockholm - Nienhuis,Frances Victoria; Bogunovic,Nina (2026)
This thesis investigates how the roles, relationships, and coordination mechanisms among stakeholders influence the integration of energy resilience in urban development (UD) projects, a challenge increasingly recognised as governance-related rather than technical. Drawing on stakeholder and resilience theory, the thesis explores how stakeholders interpret their positions and influence within UD projects through 15 semi-structured interviews and a comparative case study of Copenhagen and Stockholm. The findings reveal that most professional contributors operate in advisory roles without decision-making authority, while investment authority is concentrated among private actors and executive management. Coordination proceeds along two complementary tracks: formal mechanisms ensure accountability, while informal mechanisms provide the flexibility that formal structures cannot offer, with trust as the fundamental condition for the informal layer to function. The timing of stakeholder involvement is a critical determinant: engagement before the master plan is finalised enables co-creation, whereas late entry structurally shifts actors from partners to suppliers. Institutional barriers, such as the lack of a mandate, budget, and authority for resilience functions, mean that financial considerations typically take precedence over resilience considerations, regardless of individual motivation. A key finding is that resilience is not lost primarily at the moment of trade-off, but earlier, when organisational goals are set, roles are assigned, and coordination structures are established. These findings are summarised in a revised empirical framework that outlines the relational and institutional conditions influencing whether resilience is integrated or overlooked in UD projects. Keywords: Energy resilience, Urban Development, Stakeholder Coordination, Timing of Involvement, Decision-making Authority, Trust, Institutional Barriers, Copenhagen, Stockholm
Keywords: Energy resilience; Urban Development; Stakeholder Coordination; Timing of Involvement; Decision-making Authority; Trust; Institutional Barriers; Copenhagen; Stockholm